Fluorescent polarization assay, two versions of indirect and competitive enzyme- linked immunoassay for brucellosis diagnosis in vaccinated buffaloes (bubalus bubalis) - Martínez, Diana Elina (2021)
Fil: Martínez, Diana Elina. Universidad Nacional del Nordeste. Facultad de Ciencias Veterinarias; Argentina.